OPTIMASI KEUNTUNGAN USAHA TERNAK AYAM RAS BROILER DENGAN PROGRAM LINEAR: STUDI KASUS PADA USAHA TERNAK AYAM RAS BROILER MILIK BAPAK HUMALA PONTAS DI DESA BATUGANA - Suhaimi, Syech; Afnaria, Afnaria; Sari, Rina Filia; Marlina, Wenni; Usna, Wilia (Universitas Islam Sumatera Utara, 2024)
This research is to determine optimal profits in the Humala Pontas broiler chicken farming business by using linear programming, especially the simplex method, to solve this problem. The software used is POM-QM. The results of this research show that there is an increase in profits obtained if you apply a linear program in the feed management process. The optimal profit obtained by implementing a linear program is Rp 86,460,940.00 for one harvest. The profit so far obtained by breeders is Rp. 84. 200,000.00. There is a profit difference of Rp. 2,260,940.00 by implementing a linear program in the feed and medicine management process.